Increased number of circulating exosomes and their microRNA cargos are potential novel biomarkers in alcoholic hepatitis - Momen-Heravi, Fatemeh; Saha, Banishree; Kodys, Karen; Catalano, Donna; Satishchandran, Abhishek; Szabo, Gyongyi (Journal of translational medicine, 2015)
It has been well documented that alcohol and its metabolites induce injury and inflammation in the liver. However, there is no potential biomarker to monitor the extent of liver injury in alcoholic hepatitis patients. MicroRNAs (miRNAs) are a class of non-coding RNAs that are involved in various physiologic and pathologic processes. In the circulation, a great proportion of miRNAs is associated with extracellular vesicles (EVs)/exosomes. Here, we hypothesized that the exosome-associated miRNAs can be used as potential biomarkers in alcoholic hepatitis (AH). Exosomes were isolated from sera of alcohol-fed mice or pair-fed mice, and plasma of alcoholic hepatitis patients or healthy controls by ExoQuick. The exosomes were characterized by transmission electron microscopy and Western blot and enumerated with a Nanoparticle Tracking Analysis system. Firefly™ microRNA Assay was performed on miRNA extracted from mice sera. TaqMan microRNA assay was used to identify differentially expressed miRNAs in plasma of cohort of patients with AH versus controls followed by construction of receiver operating characteristic (ROC) curves to determine the sensitivity and specificity of the candidates. The total number of circulating EVs was significantly increased in mice after alcohol feeding. Those EVs mainly consisted of exosomes, the smaller size vesicle subpopulation of EVs. By performing microarray screening on exosomes, we found nine inflammatory miRNAs which were deregulated in sera of chronic alcohol-fed mice compared to controls including upregulated miRNAs: miRNA-192, miRNA-122, miRNA-30a, miRNA-744, miRNA-1246, miRNA 30b and miRNA-130a. The ROC analyses indicated excellent diagnostic value of miRNA-192, miRNA-122, and miRNA-30a to identify alcohol-induced liver injury. We further validated findings from our animal model in human samples. Consistent with the animal model, total number of EVs, mostly exosomes, was significantly increased in human subjects with AH. Both miRNA-192 and miRNA-30a were significantly increased in the circulation of subjects with AH. miRNA-192 showed promising value for the diagnosis of AH. Elevated level of EVs/exosomes and exosome-associated miRNA signature could serve as potential diagnostic markers for AH. In addition to the biomarker diagnostic capabilities, these findings may facilitate development of novel strategies for diagnostics, monitoring, and therapeutics of AH.